The impact of Eid al-Adha (feast of the sacrifice) sales on the income of cattle fattening enterprises (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
The objective of this project is to identify the impacts of the 120 cattle fattening enterprises operating in Ankara by the years 2010, 2011 and 2012 on the total revenue of the sales made during the period of the Eid al-Adha. The survey findings conducted on the cattle fattening enterprises operating in the 13 districts and various villages affiliated with these districts and the data derived from the survey constitute the material of the research. While for the years 2010, 2011 and 2012, the average carcass cutting price is 17.35 Turkish liras, 15.06 Turkish liras, 14.15 Turkish liras, the average carcass price in the retail sales during the Feast of Sacrifice is successively 23.07 Turkish liras; 20.02 Turkish liras; 18.44 Turkish liras; For the years 2010, 2011, and 2012 the amount of production is 2,934,293 (Kilogram) kg, 2,873,617 kg and 2,851,751 kg. Within the survey, the total revenue is successively 58,292,868 Turkish liras; 49,653,823 Turkish liras and 45,770,314 Turkish liras in the cattle fattening enterprises by the years 2010, 2011 and 2012. Of the said revenue, 50.8% (29,535,136 Turkish liras) comes from the revenue of the Eid al-Adha in 2010, 51.9% (25,740,034 Turkish liras) in 2011, and 50.9% (23,288,724 Turkish liras) in 2012